The efficiency and possibilities of development on family farms with dairy production - Zoran Grgić (Mljekarstvo)
In this work the procedure of specialised survey on the capacities andincome in dairy production as well as basic economic indicators of economic efficiency and possibilities of development estimation on family farm is presented. The survey includes the data on labour work, agricultural land, agricultural objects, the mechanisation, livestock, revenues and expenditures in farming and livestock production, as well as other incomes in households. The economic indicators, pricing system, income, profit and free capital for investing are estimated on the basis of data obtained from the survey. The procedure of data collecting and analysis from survey is very simple way of estimation of economic efficiency of major part of family farms in Croatia, which don’t use bookkeeping records.